Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 2000
DOI: 10.1115/2000-gt-0263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reynolds Number and Free-Stream Turbulence on Boundary Layer Transition in a Compressor Cascade

Abstract: An experimental and analytical study has been performed on the effect of Reynolds number and free-stream turbulence on boundary layer transition location on the suction surface of a controlled diffusion airfoil (CDA). The experiments were conducted in a rectilinear cascade facility at Reynolds numbers between 0.7 and 3.0×106 and turbulence intensities from about 0.7 to 4%. An oil streak technique and liquid crystal coatings were used to visualize the boundary layer state. For small turbulence le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…point of maximum velocity), as the Reynolds number was increased. Similar conclusions were obtained from the analytical studies performed on a compressor cascade by Schreiber et al (2002). The blade profile used had a design inlet Mach number of 0.6, a flow turning of 16° and a suction peak at 30% chord.…”
Section: Intensitysupporting
confidence: 73%
See 1 more Smart Citation
“…point of maximum velocity), as the Reynolds number was increased. Similar conclusions were obtained from the analytical studies performed on a compressor cascade by Schreiber et al (2002). The blade profile used had a design inlet Mach number of 0.6, a flow turning of 16° and a suction peak at 30% chord.…”
Section: Intensitysupporting
confidence: 73%
“…scale are 4% and 0.4B x for this grid (Mahallati, 2003). Different compressor cascades Inlet Flow at -1.2B x Outlet Flow at 1.6B x 6 6 7 7 8 8 (Küsters et al, 1999;Köller et al, 2000;Schreiber et al, 2002) and turbine cascades (Zoric, 2006;Gregory-Smith and Cleak, 1992) investigators studied the effects of freestream turbulence intensity on the secondary flows showed that it had little influence in the range of the Reynolds numbers experienced in the present study. Based on these investigations, it is assumed that the freestream turbulence intensity has little effect on the secondary flows in the present study.…”
Section: Inlet and Outlet Flow Qualitymentioning
confidence: 63%
“…According to the profile loading distribution, the blades are subjected to an 8 kg force, yielding negligible torque and stress values. Figure 11 shows the vanes installed on the window using a set of vane mounts (1), self-lubricating bronze bearings (2,3,4), and an O-ring (5). Tolerances of the blademount interface are critical, as every 5 lm translates to 0.1 deg rotation of the vane trailing edge, resulting in a 1% change in throat area.…”
Section: Mechanical Designmentioning
confidence: 99%
“…Addressing these issues, there are a limited number of continuous transonic turbine research rigs, capable of operating in various Reynolds conditions. Regardless of operational principle, a noninclusive list of existing transonic linear cascade facilities in academic institutions is provided in Table 1 [1][2][3][4][5][6][7][8][9][10][11][12]. The only heated test rigs among them are in Ecole Polytechnique Federal de Lausanne and Virginia Tech [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the need for load on compressor is increasing, which makes the reversed pressure gradient near the suction surface in the passage gradually increase, resulting in a significant rise of the three-dimensional character and the complexity of flow, and the development of the boundary layer separation and transition becomes more sensitive with external factors. Schreiber et al [4] studied the effect of Reynolds number and turbulence intensity on boundary layer transition using a surface flow visualization test method. They considered the position and geometric characteristics of the transition phenomenon and pointed out that it was necessary to pay attention to the characteristics of locations and geometry such as the starting location of transition and the width of laminar separation bubbles.…”
Section: Introductionmentioning
confidence: 99%